2015
DOI: 10.1002/wea.2468
|View full text |Cite
|
Sign up to set email alerts
|

ManUniCast: a real-time weather and air-quality forecasting portal and app for teaching

Abstract: ManUniCast is a real‐time weather and air‐quality forecasting portal developed for education and outreach at the University of Manchester. The web portal http://manunicast.com displays model output from a weather research and forecast (WRF) simulation with 20km horizontal grid spacing over the North Atlantic and Europe, including a 4km nest over the UK and Ireland. Also available is output from a WRF‐Chem simulation at 12km grid spacing over the UK. The portal displays over 60 different meteorological, chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The Tiedke cumulus parameterization scheme (Tiedtke 1989;Zhang et al 2011) was used on the outermost two grids only. These choices of parameterizations have been used for an operational model over Europe (ManUniCast; Schultz et al 2015) and have demonstrated reasonable success at forecasts of convection over Europe during the past five years of real-time model operation. Atmospheric initial and boundary conditions were provided from the ERA-40 reanalysis (Uppala et al 2005) land surface initialization was specified by the ERA-20C reanalysis (Poli et al 2016).…”
Section: Numerical Model Descriptionmentioning
confidence: 99%
“…The Tiedke cumulus parameterization scheme (Tiedtke 1989;Zhang et al 2011) was used on the outermost two grids only. These choices of parameterizations have been used for an operational model over Europe (ManUniCast; Schultz et al 2015) and have demonstrated reasonable success at forecasts of convection over Europe during the past five years of real-time model operation. Atmospheric initial and boundary conditions were provided from the ERA-40 reanalysis (Uppala et al 2005) land surface initialization was specified by the ERA-20C reanalysis (Poli et al 2016).…”
Section: Numerical Model Descriptionmentioning
confidence: 99%
“…It was only in this study that certain students expressed their interest to learn about weather forecast and to visit the weather bureau. Other scholars have attempted to create online weather and air-quality forecasting resources [22,23]. These resources, if made available to the public, could be employed for this course to facilitate the learning of weather forecasting.…”
Section: Discussionmentioning
confidence: 99%
“…Harrison et al designed a learning resource which could engage primary school students in gathering and analyzing air quality data from official air quality website [22]. Schultz et al developed a similar learning resource earlier called ManUniCast which is essentially a realtime weather and air-quality forecasting portal [23]. Gumala et al conducted a study among pre-service elementary school teachers to examine their conception of air pollution [24].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, critically assessing model results and their value is a crucial skill of a meteorologist in view of the large data volume available in the forecasting cycle. Hence, this skill must be properly trained in our course to achieve the following educational goals for students (Schultz et al 2015):…”
Section: Model Interpretation and Model Verificationmentioning
confidence: 99%